1984
DOI: 10.1007/bf01044350
|View full text |Cite
|
Sign up to set email alerts
|

Due process vs. crime control: Death qualification and jury attitudes.

Abstract: Juries that exclude people who are unwilling to impose the death penalty (death-qualified juries) may be biased against capital defendants. To evaluate this possibility we compared the demographic characteristics and attitudes toward the criminal justice system of people who would or would not be excluded by the Witherspoon standard. A random sample of 811 eligible jurors in Alameda County, Calitbrnia were interviewed by telephone. Of the 717 respondents who stated that they could be fair and impartial in deci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
148
3

Year Published

1993
1993
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(160 citation statements)
references
References 10 publications
9
148
3
Order By: Relevance
“…Specifically, a person who opposes the death penalty is likely to exhibit other attitudes that are associated with an emphasis on due process guarantees in the criminal justice system. For example, in comparison to people who oppose the death penalty, people who favor capital punishment tend to be more concerned about high levels of violent crime, to exhibit less sympathy for criminal defendants, to be more suspicious of defense attorneys, and to exhibit more favorable attitudes toward prosecuting attorneys and the police (Bronson, 1970;Fitzgerald & Ellsworth, 1984;Tyler & Weber, 1982;Vidmar & Ellsworth, 1974). It has been argued (Ellsworth & Ross, 1983;Tyler & Weber, 1982) that attitudes toward the death penalty are an especially pure example of "symbolic attitudes" (Sears & Kinder, 1971), emotionally based attitudes that serve to express a person's ideological self-image -as a practical person who takes a no-nonsense approach to crime or as a champion of the individual against the mistakes and prejudices of the state.…”
Section: Attitudes As Individual Differencesmentioning
confidence: 99%
“…Specifically, a person who opposes the death penalty is likely to exhibit other attitudes that are associated with an emphasis on due process guarantees in the criminal justice system. For example, in comparison to people who oppose the death penalty, people who favor capital punishment tend to be more concerned about high levels of violent crime, to exhibit less sympathy for criminal defendants, to be more suspicious of defense attorneys, and to exhibit more favorable attitudes toward prosecuting attorneys and the police (Bronson, 1970;Fitzgerald & Ellsworth, 1984;Tyler & Weber, 1982;Vidmar & Ellsworth, 1974). It has been argued (Ellsworth & Ross, 1983;Tyler & Weber, 1982) that attitudes toward the death penalty are an especially pure example of "symbolic attitudes" (Sears & Kinder, 1971), emotionally based attitudes that serve to express a person's ideological self-image -as a practical person who takes a no-nonsense approach to crime or as a champion of the individual against the mistakes and prejudices of the state.…”
Section: Attitudes As Individual Differencesmentioning
confidence: 99%
“…Other studies have shown that death qualification excludes certain demographic and attitudinal subgroups from capital jury service, which results in juries that are less representative, and, consequently, more biased (Hans, 1986;Moran & Comfort, 1986). In addition, death-qualified jurors are more likely to be pro-prosecution, and, consequently, pro-conviction than their excludable counterparts Fitzgerald & Ellsworth, 1984;Thompson et al, 1984).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, death-qualified jurors, when compared to their excludable counterparts, were more likely to favor the arguments made by the prosecution, mistrust defendants and defense attorneys, endorse a punitive approach toward offenders, place more importance on crime control than due process, and express less regret concerning erroneous convictions and more regret concerning erroneous acquittals (Fitzgerald & Ellsworth, 1984;Thompson, Cowan, Ellsworth, & Harrington, 1984).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, a review of Law and Human Behavior's back issues uncovered only a handful of articles directly pertaining to race or ethnicity, most of them in a special issue on discrimination edited by sociologist John Hagan in 1985. Race has been studied along with other factors in the perennial psychology-law topics of eyewitness identification (Brigham, 1980;Brigham & Ready, 1985) and jury decision making (Fitzgerald & Ellsworth, 1984;Hans & Vidmar, 1986). But systematic analysis of race and ethnicity appears to be more common in other social scientific approaches to law, and even in other subfields of psychology, than in psychology and law.…”
Section: Race and Ethnicity In The Field Of Psychology And Lawmentioning
confidence: 99%